Mental Health Response in Haiti in the Aftermath of the 2010 Earthquake: A Case Study for Building Long-Term Solutions - Raviola, Giuseppe (Informa Healthcare, 2012)
Significant challenges exist in providing safe, effective, and culturally sound mental health and psychosocial services when an unforeseen disaster strikes in a low-resource setting. We present here a case study describing the experience of a transnational team in expanding mental health and psychosocial services delivered by two health care organizations, one local (Zanmi Lasante) and one international (Partners in Health), acting collaboratively as part of the emergency response to the 2010 Haiti earthquake. In the year and a half following the earthquake, Zanmi Lasante and Partners in Health provided 20,000 documented individual and group appointments for mental health and psychosocial needs. During the delivery of disaster response services, the collaboration led to the development of a model to guide the expansion and scaling up of community-based mental health services in the Zanmi Lasante health care system over the long-term, with potential for broader scale-up in Haiti. This model identifies key skill packages and implementation rules for developing evidence-based pathways and algorithms for treating common mental disorders. Throughout the collaboration, efforts were made to coordinate planning with multiple organizations interested in supporting the development of mental health programs following the disaster, including national governmental bodies, nongovernmental organizations, universities, foreign academic medical centers, and corporations. The collaborative interventions are framed here in terms of four overarching categories of action: direct service delivery, research, training, and advocacy. This case study exemplifies the role of psychiatrists working in low-resource settings as public health program implementers and as members of multidisciplinary teams. (Harv Rev Psychiatry 2012;20:68–77.)